Variability of Surface Level Particulate Matterin Kathmandu and Pokhara and an Overview of Origin of Pollutants - Regmi, Jeevan; Poudyal, Khem N.; Pokhrel, Amod; Wilson, Katrina; Aryal, Rudra (Journal of Engineering and Sciences, 2022)
Abstract available with full text.